Contralateral relapse after surgery for breast cancer: evaluation of follow‐up paradigms. Issue 11 (24th October 2013) - Kontos, M.; Roy, P.; Rizos, D.; Petrou, A.; Hamed, H.
Summary: Background: Early treatment of breast cancer patients with loco‐regional relapse or contralateral disease has been shown to improve survival. There is no current consensus on the optimal follow‐up strategy. This study estimates the risk of isolated contralateral relapse (CR) after breast cancer surgery and its change over time, together with the efficacy of clinical examination, self‐examination and mammography in the detection of CR. Methods: Data from patients treated for early breast cancer at Guy's Hospital between 1990 and 1997 were collected and those with isolated contralateral recurrences were analysed. Life table analysis was performed and CR, CR‐free and cumulative CR rates were calculated. Correlations were evaluated using Pearson's correlation coefficient. Results: One thousand one hundred and forty‐three women were included in the study and 23 patients had isolated CR. The median probability of CR was a constant 0.24% per year. Only one recurrence was found clinically at follow up, while the majority was detected through mammography and self‐palpation. Conclusions: The risk of CR is low and constant with time. Contralateral mammography is useful and can detect the vast majority of contralateral recurrences. These findings may have practical implications especially on the planning of postmastectomy follow up. Abstract : Linked Comment:Fentiman. Int J Clin Pract 2013; 67: 1071–2 .